KOLABORASI STAKEHOLDER DALAM PENYEDIAAN PERUMAHAN UNTUK MASYARAKAT BERPENGHASILAN RENDAH DI KOTA SALATIGA - S Sunarti; Nany Yuliastuti; I Indriastjario (Diponegoro University, 2018)
Land limitations in urban areas have caused low-income communities unable to easily own a house. The high price of land has become the most influential factor in house prices, not including the costs for the facilities and infrastructure construction. Salatiga as a small city in Central Java in providing housing for civil servants has collaborated with all stakeholders. This study aims to form a stakeholder collaboration model in the provision of affordable housing for low-income communities in Salatiga. The research method used is qualitative, which explores data from the informants involved in the construction of housing for civil servants and the analysis technique used was stakeholder analysis and qualitative descriptive analysis. The results of the study formulated that stakeholder collaboration in providing housing for civil servants in the Salatiga City consists of three group of stakeholders, namely, key, main and supporting stakeholders. Key stakeholders were the Mayor as the party who recommended the release of the government land assets to the community, Regional House of Representatives of Salatiga as the party who give agrement of disposal assets, and the civil servant housing development coordination team, namely members of KORPRI who coordinate all housing development implementation activities. The main stakeholders were civil servants as prospective homeowners. Supporting stakeholders were developers and local government agencies that provide construction program in the construction of houses, facilities, and infrastructure in the Prajamulia and Prajamukti housing in the Salatiga.